Hugo RAS Versus Da Vinci in Colorectal Surgery: A Systematic Review and Outcome Meta-Analysis - Sascha Vaghiri; Dimitrios Prassas; Emmanuella Habib; Norma Schmitz-Conti; Wolfram Trudo Knoefel; Andrea Alexander (Journal of Clinical Medicine, 2026)
Background: The advantages of robotic surgery have increasingly led to its rapid adoption in surgical practice. In this context, new robotic platforms such as Hugo RAS have been introduced in recent years to meet the demand for cost-effective alternatives to the well-established Da Vinci system. However, high-quality evidence directly comparing the operative outcomes of these platforms remains scarce. Methods: The current PRISMA and Cochrane guidelines were followed. After careful study selection using the MEDLINE, Scopus, Google Scholar, and Cochrane Register databases, relevant operative and oncologic outcomes were extracted and analyzed from suitable studies comparing the Hugo RAS and Da Vinci platforms in colorectal surgery. ROBINS-I and GRADE were applied to judge the risk of bias and evidence level, respectively. Results: Five comparative studies with a total of 370 patients (Hugo RAS: n = 130; Da Vinci: n = 240) were included in the final analysis. Operative duration (min) was significantly longer in the Hugo RAS cohort than in Da Vinci procedures (MD 25.98, 95% CI: 6.35–4.62; p = 0.009; I2 = 38%). Other endpoints, including the duration of hospitalization, operative morbidity, and oncological parameters, were comparable between the groups, although considerable heterogeneity was observed for length of hospital stay. The amount of blood loss (mL) was reported to be lower in the Da Vinci group in four studies, whereas one study found lower blood loss in the Hugo RAS group, resulting in conflicting findings and substantial heterogeneity across the included studies. The overall risk of bias ranged from moderate to serious. Conclusions: The results presented here suggest that colorectal surgery using the modular Hugo RAS platform is technically reliable and effective with apparently comparable perioperative outcomes to the Da Vinci system. Nevertheless, serious methodological and statistical limitations, as well as inter-study heterogeneity, warrant further high-quality, standardized, multi-institutional studies.